Teachers' perception on empowerment / Aida Noor Izam Bujang - Bujang, Aida Noor Izam (2012)
Education reform is taking place in almost every country and Malaysia is excluded from this. Education reform has brought to the concept of empowerment to the school staff. The purpose of this study was to determine the perceived degree of teacher empowerment in public school and to identify the obstacle and facilitators to their teacher empowerment. The data were collected through a questionnaire returned by a sample of 69 public teachers using School Participant Empowerment Scale (SPES), adopted from Short & Rinchart (1992).